Benzonate derivatives of acetophenone as potent α-glucosidase inhibitors: synthesis, structure-activity relationship and mechanism - Wen-Jia Dan; Qiang Zhang; Fan Zhang; Wei-Wei Wang; Jin-Ming Gao (Taylor & Francis Group, 2019)
In this article, 23 compounds (6 and 7a-7v) were prepared and evaluated for their in vitro α-glucosidase inhibitory activity. The compounds 7d, 7f, 7i, 7n, 7o, 7r, 7s, 7u, and 7v displayed the α-glucosidase inhibition activity with IC50 values ranging from 1.68 to 7.88 µM. Among all tested compounds, 7u was found to be the most efficient, being 32-fold more active than the standard drug acarbose, which significantly attenuated postprandial blood glucose in mice. In addition, the compound 7u also induced the fluorescence quenching and conformational changes of enzyme, by forming α-glucosidase-7u complex in a mixed inhibition type. The thermodynamic constants recognised the interaction between 7u and α-glucosidase and was an enthalpy-driven spontaneous exothermic reaction. The synchronous fluorescence and CD spectra also indicate that the compound 7u changed the enzyme conformation. The findings identify the binding interactions between new ligands and α-glucosidase and reveal the compound 7u as a potent α-glucosidase inhibitor.